Robust and stretchable self-healing polyurethane based on polycarbonate diol with different soft-segment molecular weight for flexible devices. (September 2019) - Ha, Yu-mi; Kim, Young-O; Ahn, Seokhoon; Lee, Seoung-ki; Lee, Jae-suk; Park, Min; Chung, Jae Woo; Jung, Yong Chae
Graphical abstract: Highlights: We developed a novel self-healing and shape memory polyurethane elastomer with superior mechanical properties by controlling the different molecular weight of the polyol and incorporating dynamic disulfide bonds for reversibility. We have identified a potential application for the self-healing flexible substrate in flexible electronics. Abstract: The self-healing polyurethane films have received significant attention due to their unique shape memory behaviors and the hydrogen bonding arising from the urethane linkages. However, it is still a challenge to develop self-healing polyurethane with transparent, high impact resistance, and excellent shape recovery and mechanical properties. In particular, polycarbonate-based polyurethane shows transparency, weatherability and excellent mechanical properties. In this work, transparent self-healing polyurethane film with robust mechanical properties (breaking stress of 26 MPa and elongation at break of 630%) was synthesized by controlling the different molecular weight of the polycarbonate diol and incorporating dynamic disulfide bonds for reversibility. As a result, the self-healing polyurethane film showed an excellent self-healing ability with 98% healing efficiency and excellent shape memory ability with a recovery efficiency of ˃92%. In addition, we have identified a potential application for the self-healing flexible substrate in flexible electronics because of their stable electrical resistance even upon mechanical deformation.